Inspection of birefringence characteristics to establish single-mode fiber quality - Zairmi, Yoli; Basdyo, Doni; Hairi, Haryana Mohd; Aziz, Muhammad Safwan Abd; Abdullah, Hewa Yaseen (Science, Technology and Communication Journal, 2022)
Birefringence characterization has been carried out for single-mode fiber (SMF) consisting of SMF-28, SMF-28e, SMF-28e+, SMF-28e+LL, and SMF-28ULL. The parameters that were varied were the refractive index of the core and the cladding, while the radii of both were equal to the wavelength of 1550 nm. Birefringence characterized by simulation can determine the quality of SMF by knowing the changes in the light propagation constant caused by polarized light on optical fibers. The simulation results show that in SMF-28ULL there is a propagation constant or birefringence which has a large influence compared to other types of SMF such as the magnitude of polarization and reducing power.